2017
DOI: 10.1590/s1518-8787.2017051000011
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with self-reported diabetes according to the 2013 National Health Survey

Abstract: OBJECTIVES To analyze the factors associated with self-reported diabetes among adult participants of the National Health Survey (PNS).METHODS Cross-sectional study using data of the PNS carried out in 2013, from interviews with adults (≥ 18 years) of 64,348 Brazilian households. The prevalence of self-reported diabetes, assessed by the question “Has a doctor ever told you that you have diabetes?,” was related to sociodemographic characteristics, lifestyle, self-reported chronic disease, and self-evaluation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0
34

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(68 citation statements)
references
References 30 publications
(39 reference statements)
5
29
0
34
Order By: Relevance
“…Extrapolation of our results to the adolescent population in cities with more than 100 000 inhabitants resulted in 200 000 living with T2DM and almost 1.5 million with prediabetes, a condition that has been shown to increase cardiovascular risk in this population . Several previous studies have reported a rapid increase in the prevalence of diabetes in Brazil, mostly in adults . However, most of these studies were based on self‐reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extrapolation of our results to the adolescent population in cities with more than 100 000 inhabitants resulted in 200 000 living with T2DM and almost 1.5 million with prediabetes, a condition that has been shown to increase cardiovascular risk in this population . Several previous studies have reported a rapid increase in the prevalence of diabetes in Brazil, mostly in adults . However, most of these studies were based on self‐reports.…”
Section: Discussionmentioning
confidence: 99%
“…30 Several previous studies have reported a rapid increase in the prevalence of diabetes in Brazil, mostly in adults. 5,31 However, most of these studies were based on self-reports. Also, because the American Diabetes Association only included HbA1c as a criterion for diabetes in 2009, 32 most past studies did not consider HbA1c in their diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated the association between diabetes and non-localized obesity, characterized by a high body mass index 40,41 . The growing obesity in the Brazilian population has contributed to the rise of diabetes and population ageing 42 .…”
Section: Discussionmentioning
confidence: 99%
“…Considerando o rápido envelhecimento da população brasileira, é importante o investimento em programas de promoção, visando a intervenções precoces, para prevenir e controlar o DM, tais como: alimentação saudável, restrição do tabaco e consumo de álcool e programas para a prática de atividade física. Assim contribuirá na redução do sobrepeso e obesidade e outros fatores de risco comuns às Doenças Crônicas Não Transmissíveis (DCNT), como o DM (4) .…”
Section: Introductionunclassified